Indices of homeostasis in cattle after treatment with supramolecular complex of fenbendazole - A. I. Varlamova; I. A. Arkhipov (Российский паразитологический журнал, 2019)
The purpose of the research: to study the tolerability of supramolecular complex of fenbendazole (SMCF) by cattle. Materials and methods. Research was conducted in Tepelevo from Dalnekonstantinovsky district of the Nizhny Novgorod region on 20 heifers at the age of 13-16 months. Heifers was divided on the principle of analogs into 4 groups of 5 animals each. The animals of groups 1, 2 and 3 were given a single oral dose of SMCF at a dose of 2, 6 and 10 mg/kg, i.e. in therapeutic dose, 3 and 5 times increased doses. Heifers of the fourth group did not receive the drug and served as a control. Clinical, hematological and biochemical indices of young cattle of all groups were studied one day before and after 1, 3 and 5 days after administration of the drug using standard methods. Results and discussion. SMCF in therapeutic, in 3 and 5 times increased doses does not adversely affect the clinical, hematological and biochemical indices of young cattle. The condition of animals receiving the drug in doses of 2, 6 and 10 mg/kg was within the physiological norm and did not differ from the state of control animals. Drug safety index greater than 5. The number of red blood cells, white blood cells, hemoglobin, leukogram performance and blood biochemical parameters: the activity of alkaline phosphatase, amylase, bilirubin, creatinine, urea and glucose levels were within normal limits and did not differ from control animals.